The influence of dehydration conditions on the quality of dried bell peppers (Capsicum annuum) - Sigge, G. O. (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Sc. in Voedselwetenskap) -- Universiteit van Stellenbosch, 1996.